Cash and COVID-19: What happened in 2021 - Heng Chen; Walter Engert; Kim P. Huynh; Daneal O'Habib; Joy Wu; Hui Zhu (Bank of Canada, 2022)
We provide an update on the impact the COVID-19 pandemic on the demand for cash and the use of methods of payment based on data from the Bank Note Distribution System and from consumer surveys conducted in April and August 2021. Our key findings are as follows: Cash in circulation remained high throughout 2021, driven mainly by demand for largedenomination notes; Canadians' holdings of cash on hand in April (median 70) and August (median 80) were comparable to results seen in 2020. Other cash holdings reported by Canadians remained elevated, with a median value of 260 in August; In August 2021, 62% of Canadians used cash for payments, and indicators of merchant acceptance of cash improved in both the April and August surveys; A large majority of Canadians (around 80%) in 2021 continued reporting that they have no plans to go cashless in the next five years.
Keywords: C; C1; C12; C9; E; E4; O; O5; O54; 330; Bank notes; Central bank research; Coronavirus disease (COVID-19); Digital currencies and fintech; Econometric and statistical methods